Determining Illocutionary Act with VARIES Models - Theresia Fransiska Zai; Rahmadsyah Rangkuti; Dian Marisha Putri (LingPoet: Journal of Linguistics and Literary Research, 2021)
Research on the use of language is growing over time as many theories of language use are found. Language is no longer just for communicating but identifying something either implicitly or not. This paper discusses the language use to identify the act of utterance by knowing the context and social background in panel discussion conducted by descriptive qualitative approach with content analysis method and focused on language use based on the phenomenon of the panel discussion. The data in this study was in the form of utterance containing lexical items which is used to refer to speakers’ language uses in conveying social background and action. This research applied sociopragmatic approach to analyze speakers' social background using VARIES Model theory and speakers's meaning using Illocutionary Act theory through language use. The result of this study shows that vocational language can determine acts such as representative, expressive, directive speech act; age language to directive speech act; religion language to representative, directive and expressive speech act; informality language to representative, expressive and declarative speech act; education background to representative, directive, expressive, commissive speech act; sex language to representative, directive, commissive, expressive and declarative speech act